2021
DOI: 10.22271/phyto.2021.v10.i1m.13451
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis in rice breeding lines for yield and its components using principal component analysis

Abstract: One hundred and nineteen rice breeding lines with two local checks were subjected to the principle component analysis (PCA) and cluster analysis to estimate the existing genetic diversity for yield contributing characters. The first three principal components having Eigen value more than one are cumulatively contributing 68.69% to the total variability. PC1 has the contribution from the traits days to 50% flowering (0.497), days to maturity (0.484) and ear bearing tillers (0.359) which accounted 31.84% of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Nevertheless, developing rice for tolerance to drought stress through breeding is a sustainable and cost-effective approach in improving its productivity [17]. Several efforts have been made to improve drought tolerance by identifying donor genotypes, but success rate for their translation into drought-tolerant varieties is very low [18]. For example, screening a large set of genotypes at International Rice Research Institutes (IRRI) of different origins showed that most of the drought-tolerant accessions identified were of aus and indica types that belong to India, Bangladesh, and Sri Lanka [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, developing rice for tolerance to drought stress through breeding is a sustainable and cost-effective approach in improving its productivity [17]. Several efforts have been made to improve drought tolerance by identifying donor genotypes, but success rate for their translation into drought-tolerant varieties is very low [18]. For example, screening a large set of genotypes at International Rice Research Institutes (IRRI) of different origins showed that most of the drought-tolerant accessions identified were of aus and indica types that belong to India, Bangladesh, and Sri Lanka [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is also grown with irrigation in locations where rainfall is scarce. Rice is a staple cuisine in India's eastern and southern regions [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The first three principal components (PC1, PC2 and PC3) were considered as the major principal components as their eigen values were more than one. Similarly, Kumari et al (2021) reported that the first three principal components as a major principal component while studying 121 rice germplasm. The eigen values and contribution per cent towards divergence are presented in Table 1 and Fig The scatter plot was constructed using the first two major principal components that constituted 600 germplasm scatter along with the ten traits (Fig.…”
Section: Resultsmentioning
confidence: 95%